An analysis of reputation, predictability, and perceived risk on user trust in telemedicine consultation services - Husna, Arina Himatul; Faladhin, Johan; Marsya, Ulmi (Interaksi: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the impact of reputation, predictability, and risk on user trust in telemedicine consultation services. User trust is a crucial factor in the adoption and sustainability of telemedicine services. This research uses Perceived Risk Theory to explore the effects of risk on user perceptions and examines how reputation and predictability influence trust. The method employed is a quantitative survey with questionnaires distributed to telemedicine service users between January 16 and February 16, 2023. The unit of analysis in this study is users who have utilized telemedicine services, especially in health consultation, at least once. The findings reveal that the combined contribution of the three variables (reputation, predictability, and risk) to user trust is 25.7%, as indicated by the coefficient of determination (R²). This means that 74.3% of user trust is influenced by factors outside of reputation, predictability, and risk, such as service quality, user experience, and direct interaction with service providers. This research provides insights that while these three variables have a significant impact, other factors also play a crucial role in building user trust in telemedicine consultation services.